Patient-reported disease impact of systemic lupus erythematosus with active joint symptoms: Results from the systemic lupus erythematosus-update survey. (March 2023) - Kamen, Diane L; Birt, Julie A; Hadi, Monica A; Gibbons, Elizabeth; Bushnell, Donald M; Yu, Ren; Delbecque, Laure A; Griffing, Kirstin; Askanase, Anca
Background: Many people with systemic lupus erythematosus (SLE) experience joint pain, swelling, and stiffness. These joint symptoms are associated with problems in physical functioning and work disability. We used survey data from adults with SLE to explore the burden and impact of joint symptoms. Methods: SLE-UPDATE was a 2019 cross-sectional US survey of adults with SLE. We compared respondents with "currently active" joint symptoms' and those "without currently active" joint symptoms. The active joint cohort comprised survey respondents who self-reported current "stiffness in joints" or "pain/swelling in joints" and who had moderate to severe joint pain (Worst Joint Pain Numeric Rating Scale [NRS] score ≥ 4). Respondents not fulfilling these criteria were included in the non-active joint cohort. Outcomes included frequency and severity of pain, patient-reported outcomes (LupusPRO™ and Work Productivity and Activity Impairment: Lupus [WPAI-Lupus]), satisfaction with current treatments, and importance of different treatment goals. Results: More respondents in the active joint cohort (N = 285) than in the non-active joint cohort (N = 215) reported pain most or all the time over the preceding 7 days (77.5% vs. 32.1%, p < .0001), fibromyalgia (45% vs. 12%, p < .0001), and higher (worse) mean scores on the Worst Pain NRS (6.5 vs. 4.8, p < .0001) and Worst Joint Pain NRS (6.7 vs. 4.5, p < .0001). Mean Lupus PRO health-related quality of life (HRQoL) total score was lower (worse) in the active joint cohort (48.9 vs. 64.1, p < .0001). WPAI-Lupus scores indicated greater work productivity losses and activity impairment in the active joint cohort. More respondents in the active joint cohort than in the non-active joint cohort were neutral or not satisfied with current treatments and rated reducing pain as a "very important" treatment goal (26.7% vs. 18.1%). Conclusions: Respondents with SLE and active joint manifestations in addition to having more pain report lower HRQoL and were less satisfied with their current treatments. Comorbid fibromyalgia may play a role in joint symptoms in patient with SLE joint manifestations. There is an unmet need for new therapeutic options to reduce joint symptom burden among patients with SLE.